Implementing Neural Network on Data Mining To Predicting Key Performance Index From Employee - Albert Yakobus Chandra; Putri Taqwa Prasetyaningrum; Irfan Pratama (Publikasi Indonesia, 2022)
Employee performance could help the company success to achieve its goals. In this era predicting employee performance is a necessity for companies to gain success. In this research, we presented a prediction of the employee performance index using a neural network. In this study, we are using the Cross-industry standard process for data mining (CRISP-DM) as the base framework for the data mining phase. The neural network classification method is employed to create the prediction model. The result shows that using a neural network could get a confusion matrix at 97.777 percent. This model was then applied to get insight from the performance index that showed a couple of factors is has an important role in employee performance.